The role of polymers in genetic engineering and biotechnology applications/ A Review Article - Dr. Abdalkader Saeed Latif; Dr. Ahmed Abdulelah Ahmed; Rasha Mohamed Sajet AL-Oqaili; Huda Farooq Zaki (Peerian Journals Publishing, 2024)
The review presents how polymers play their roles in genetic engineering and biotechnological applications, including gene transfer, CRISPR-Cas9-mediated gene editing, vaccine development, and regenerative medicine. To explain how polymers contribute to the improvement of such technologies, various research methods were used, including literature review and case studies.
Keywords: Polymers; Genetic Engineering; CRISPR-Cas9; Vaccines